Literature Review: Strategies to Increase the Hiring Rate and Shorten the Waiting Period of Vocational School Graduates in Workforce - Wahid, Muchdjabir; Ratnasari, Devi (Jurnal Riset Ilmu Pendidikan, 2024)
The open unemployment rate (TPT) for graduates of Vocational High Schools (SMK) in Indonesia remains high, reaching 10.38% (BPS, 2022). This indicates a gap between the skills of SMK graduates and the demands of the business and industrial sectors (DUDI). This study aims to identify strategies for improving the absorption rate and reducing the waiting period for SMK graduates through a systematic literature review. The findings indicate that several effective strategies have been implemented, including graduate marketing through the Special Job Market (BKK), the BMW program (Work, Further Education, and Entrepreneurship), and the Link and Match model, which aligns the curriculum with industry needs. Additionally, soft skills training and teacher competency enhancement contribute to graduates' job readiness. In conclusion, synergy between SMKs, DUDI, and the government is crucial to creating a more adaptive vocational education ecosystem, ultimately enhancing graduates' competitiveness in the job market.